Manganese-based composite positive electrode material and preparation method and application thereof

The preparation of manganese-based composite positive electrode material with core-shell structure through co-precipitation method is solved, and the problems of low energy density and poor cycle stability of lithium manganese oxide materials are achieved, and a lithium-ion battery with high energy density, long life and high safety are achieved.

CN119833606APending Publication Date: 2025-04-15NINGBO FULI BATTERY MATERIAL TECH CO LTD +1
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202510025511.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

As the positive electrode material of lithium-ion batteries, lithium manganate has low energy density, poor cycle stability, and has problems of manganese dissolution at high temperatures, which limits its scale use in electric vehicles.

Method used

A manganese-based composite positive electrode material with a core-shell structure was prepared by co-precipitation method. The inner core was lithium manganate and the outer shell was a lithium-rich manganese-based positive electrode material. By pre-oxidation, lithium mixing and sintering modification, a high-capacity, high-safety and long-cycling material was formed.

Benefits of technology

The long circulation, high safety and high compaction effects of manganese-based positive electrode materials are achieved, the problems of manganese dissolution and cycle stability are solved, and the energy density of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005234571320000011
    Figure HDA0005234571320000011
  • Figure HDA0005234571320000012
    Figure HDA0005234571320000012
  • Figure HDA0005234571320000021
    Figure HDA0005234571320000021
Patent Text Reader

Abstract

The invention provides a manganese-based composite positive electrode material and a preparation method and application thereof. The manganese-based composite positive electrode material has a core-shell structure; the core of the core-shell structure is made of a lithium manganate material, and the shell is made of a lithium-rich manganese-based positive electrode material. Compared with the prior art, a manganese-based composite positive electrode material precursor with the inner core mainly comprising manganese and the outer shell mainly comprising nickel, cobalt and manganese is prepared in situ by adopting a coprecipitation method, and then pre-oxidation, lithium mixing and sintering modification are performed; the high-capacity, high-safety, long-circulation and high-compaction manganese-based composite positive electrode material of which the core is the lithium manganate material and the shell is the lithium-rich manganese-based positive electrode material is obtained, so that the problems of cycling stability and high-temperature storage of the manganese-based positive electrode material are solved; furthermore, the manganese-based composite positive electrode material is used as the positive electrode material of the lithium ion battery, so that the lithium ion battery with high energy density, long service life and high safety can be prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and more specifically to a manganese-based composite positive electrode material and a preparation method and application thereof. Background Art

[0002] In recent years, with the development of science and technology, various consumer electronic products such as smart phones, tablet computers, and electronic bracelets are changing with each passing day, the market for energy-saving and environmentally friendly electric vehicles is growing rapidly, and the energy storage battery market has emerged. The market for lithium-ion batteries, which are the power source of these products, has developed rapidly. Lithium-ion batteries are a type of secondary battery with the characteristics of green environmental protection, high energy density, and long cycle life. With the expansion of the scope of use of lithium-ion batteries and the increasing degree of dependence on them, the requirements for various performance indicators of lithium-ion batteries are becoming higher and higher, especially energy density and safety performance. Lithium manganese oxide material is a cathode material with abundant resources, low cost, good rate performance, and high safety. However, lithium manganese oxide has low energy density, poor cycle stability, and the problem of manganese dissolution at high temperature, which also limits its large-scale use in electric vehicles. Lithium-rich manganese-based cathode materials have the advantages of high specific energy, high safety, low cost, and good cycle performance. In recent years, adding an appropriate amount of lithium-rich manganese-based cathode materials to improve the cycle performance of lithium manganese oxide while increasing the energy density of the material and further improving the safety performance has become a feasible solution recognized by the industry.

[0003] At present, the existing technology mainly uses lithium manganese oxide to composite other positive electrode materials to solve the problems of low energy density and poor cycle performance of lithium manganese oxide as a power battery; such as lithium manganese oxide composite lithium iron phosphate. This composite positive electrode material can improve its cycle stability to a certain extent, but it has limited effect on improving its energy density. Increasing the operating voltage of the battery is one of the effective means to improve the energy density of the battery. Usually, due to the low compaction density of lithium iron phosphate, this type of material will have poor cycle stability under high voltage, and commercial lithium iron phosphate is carbon-coated on the surface, and carbon will react with manganese to affect the electrochemical properties of manganese-based positive electrode materials. Lithium manganese oxide composite lithium supplement material is one of the effective methods to improve its cycle performance, but after the traditional composite positive electrode material is made into a pole piece, due to long-term circulation, there will be inconsistent depths of lithium de-lithiation and lithium insertion, resulting in poor cycle stability of the pole piece. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a manganese-based composite positive electrode material and a preparation method and application thereof. The manganese-based composite positive electrode material provided by the present invention has a core-shell structure with an inner core of lithium manganese oxide and a shell layer of lithium-rich manganese base, which can play a lithium supplement role in the battery, improve the cycle stability and manganese dissolution problems of the manganese-based material, and achieve long cycle, high safety and high compaction effects of low-cost composite manganese-based positive electrode material batteries.

[0005] The present invention provides a manganese-based composite positive electrode material having a core-shell structure;

[0006] The core of the core-shell structure is a lithium manganese oxide material, and the shell is a lithium-rich manganese-based positive electrode material.

[0007] Preferably, the general formula of the manganese-based composite positive electrode material is (1-x)LiMn2O4-xLi 1+y Ni a Co b Mn c O2; wherein, 0<x≤0.15, y>0, 0<a<0.5, 0≤b<0.5, 0<c<1.

[0008] Preferably, the inner core is polycrystalline lithium manganese oxide, multiple single-crystal lithium manganese oxide or single single-crystal lithium manganese oxide; the outer shell is polycrystalline lithium-rich manganese-based positive electrode material or multiple single-crystal lithium-rich manganese-based positive electrode materials.

[0009] Preferably, the diameter of the inner core is 1 μm to 15 μm; the thickness of the outer shell is 50 nm to 500 nm; and the diameter of the core-shell structure is 1 μm to 16 μm.

[0010] The present invention also provides a method for preparing the manganese-based composite positive electrode material described in the above technical solution, comprising the following steps:

[0011] a) mixing a manganese-containing salt solution, a precipitant, and a complexing agent to perform a first coprecipitation reaction to obtain a precursor suspension containing a spherical manganese oxide material;

[0012] b) adding a mixed solution containing nickel, cobalt and manganese, a precipitant and a complexing agent to the precursor suspension containing the spherical manganese oxide material obtained in step a), and performing a second coprecipitation reaction to obtain a manganese-based composite material precursor suspension;

[0013] c) washing, filtering and drying the manganese-based composite material precursor suspension obtained in step b) to obtain a composite material precursor;

[0014] d) pre-oxidizing the composite material precursor obtained in step c) to obtain a precursor oxide;

[0015] e) solid-phase mixing the precursor oxide obtained in step d) with a lithium source and then sintering to obtain a manganese-based composite positive electrode material.

[0016] Preferably, the temperature of the first coprecipitation reaction in step a) is 50° C. to 60° C., the stirring speed is 400 r / min to 1000 r / min, the pH value is 7.5 to 11.5, and the time is 40 h to 120 h.

[0017] Preferably, the temperature of the second coprecipitation reaction in step b) is 40° C. to 60° C., the stirring speed is 700 r / min to 900 r / min, the pH value is 7.9 to 11.9, and the time is 10 h to 20 h.

[0018] Preferably, the sintering temperature in step e) is 800° C. to 1200° C., and the sintering time is 10 h to 25 h.

[0019] The present invention also provides a positive electrode plate, comprising the manganese-based composite positive electrode material described in the above technical solution.

[0020] The present invention also provides a lithium-ion battery, which uses the positive electrode sheet described in the above technical solution as a positive electrode.

[0021] The present invention provides a manganese-based composite positive electrode material and a preparation method and application thereof; the manganese-based composite positive electrode material has a core-shell structure; the core of the core-shell structure is a lithium manganate material, and the shell is a lithium-rich manganese-based positive electrode material. Compared with the prior art, the present invention adopts a coprecipitation method to in-situ prepare a manganese-based composite positive electrode material precursor with a core mainly composed of manganese and a shell mainly composed of nickel, cobalt and manganese, and then obtains a high-capacity, high-safety, long-cycle, high-density manganese-based composite positive electrode material with a core of lithium manganate material and a shell of lithium-rich manganese-based positive electrode material after pre-oxidation, lithium mixing, and sintering modification, thereby solving the problems of cycle stability and high-temperature storage of manganese-based positive electrode materials; further adopting the manganese-based composite positive electrode material as a lithium-ion battery positive electrode material can prepare a lithium-ion battery with high energy density, long life and high safety.

[0022] At the same time, the preparation method provided by the present invention has simple process, easily controllable conditions and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A flow chart of the preparation method provided in Example 1 of the present invention;

[0024] Figure 2 A schematic diagram and SEM photo of the manganese-based composite positive electrode material provided in Example 1 of the present invention;

[0025] Figure 3 A schematic diagram and SEM photo of a manganese-based composite positive electrode material provided in Example 4 of the present invention;

[0026] Figure 4 A schematic diagram and SEM photo of a manganese-based composite positive electrode material provided in Example 6 of the present invention;

[0027] Figure 5 Schematic diagram and SEM photo of the manganese-based composite positive electrode material provided in Example 5 of the present invention. DETAILED DESCRIPTION

[0028] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0030] The present invention provides a manganese-based composite positive electrode material having a core-shell structure;

[0031] The core of the core-shell structure is a lithium manganese oxide material, and the shell is a lithium-rich manganese-based positive electrode material.

[0032] In the present invention, the manganese-based composite positive electrode material is a composite positive electrode material with a core-shell structure; the core of the core-shell structure is a lithium manganate material, and the shell is a lithium-rich manganese-based positive electrode material.

[0033] In the present invention, the general formula of the manganese-based composite positive electrode material is preferably (1-x)LiMn2O4-xLi 1+ y Ni a Co b Mn c O2; wherein, 0<x≤0.15, y>0, 0<a<0.5, 0≤b<0.5, 0<c<1.

[0034] In the present invention, the core is preferably polycrystalline lithium manganese oxide, multiple single-crystal lithium manganese oxide or single single-crystal lithium manganese oxide; the shell is preferably polycrystalline lithium-rich manganese-based positive electrode material or multiple single-crystal lithium-rich manganese-based positive electrode material. In a preferred embodiment of the present invention, the core lithium manganese oxide is a secondary agglomerate particle or a single crystal particle, and the shell lithium-rich manganese-based positive electrode material is a large secondary agglomerate particle composed of secondary agglomerates; the core of the secondary agglomerate particle includes 1 to 10 secondary agglomerates or single crystal particles.

[0035] In the present invention, the diameter of the inner core is preferably 1 μm to 15 μm; the thickness of the outer shell is preferably 50 nm to 500 nm; and the diameter of the core-shell structure is preferably 1 μm to 16 μm.

[0036] In the present invention, the manganese-based composite positive electrode material adopts a simple precipitation method to synthesize a manganese oxide precursor as the core of the composite positive electrode material, and a secondary co-precipitation is used to synthesize a nickel-cobalt-manganese multi-material precursor of a lithium-rich manganese-based positive electrode material, and then pre-oxidation, lithium mixing, and sintering are performed to obtain a secondary spherical manganese-based composite positive electrode material with a core and an outer shell.

[0037] The present invention also provides a method for preparing the manganese-based composite positive electrode material described in the above technical solution, comprising the following steps:

[0038] a) mixing a manganese-containing salt solution, a precipitant, and a complexing agent to perform a first coprecipitation reaction to obtain a precursor suspension containing a spherical manganese oxide material;

[0039] b) adding a mixed solution containing nickel, cobalt and manganese, a precipitant and a complexing agent to the precursor suspension containing the spherical manganese oxide material obtained in step a), and performing a second coprecipitation reaction to obtain a manganese-based composite material precursor suspension;

[0040] c) washing, filtering and drying the manganese-based composite material precursor suspension obtained in step b) to obtain a composite material precursor;

[0041] d) pre-oxidizing the composite material precursor obtained in step c) to obtain a precursor oxide;

[0042] e) solid-phase mixing the precursor oxide obtained in step d) with a lithium source and then sintering to obtain a manganese-based composite positive electrode material.

[0043] In the present invention, the method for preparing the manganese-based composite positive electrode material is preferably as follows:

[0044] (1) mixing a manganese-containing compound with water to obtain a manganese-containing salt solution;

[0045] (2) adding the manganese-containing salt solution, precipitant, and complexing agent into a coprecipitation reactor through a metering pump, and performing a first coprecipitation reaction by controlling the reactor temperature, protective atmosphere, stirring speed, and reaction pH value to obtain a precursor suspension containing spherical manganese oxide material;

[0046] (3) mixing the nickel-containing compound, the cobalt-containing compound and the manganese-containing compound with water to obtain a mixed solution containing nickel, cobalt and manganese;

[0047] (4) adding the mixed solution containing nickel, cobalt and manganese, the precipitant and the complexing agent into the reactor containing the precursor suspension containing the spherical manganese oxide material through a metering pump, and performing a second coprecipitation reaction by controlling the temperature of the reactor, the protective atmosphere, the stirring speed and the reaction pH value to obtain a manganese-based composite material precursor suspension containing a spherical manganese oxide material as an inner core and a nickel-cobalt-manganese multi-element material as a lithium-rich manganese-based positive electrode material as an outer shell;

[0048] (5) washing, filtering and drying the manganese-based composite material precursor suspension in sequence to obtain a composite material precursor;

[0049] (6) Pre-oxidizing the composite material precursor to obtain a manganese-based composite positive electrode material precursor oxide, wherein the manganese-based composite positive electrode material precursor oxide is represented by the following general formula: Mn c Ni a Co b O2, where 0.7≤c<1, 0.1 <a<0.3,0≤b<0.3;

[0050] (7) The above-mentioned manganese-based composite positive electrode material precursor oxide is mixed with a lithium source solid phase, and sintered at a high temperature to obtain the original material of the manganese-based composite positive electrode material.

[0051] In a preferred embodiment of the present invention, for the technical solution in which the precipitant is sodium carbonate, no protective atmosphere is required, and the present invention has no special limitation on this, and the coprecipitation reaction can be carried out according to technical means well known to those skilled in the art.

[0052] In a preferred embodiment of the present invention, for the technical solution in which the core is a single single crystal lithium manganese oxide, preferably 4% to 6% of the total mass of the mixture after solid phase mixing is added as a co-solvent, and the co-solvent is preferably boric acid. The present invention has no special restrictions on the source of the co-solvent, and commercially available products known to those skilled in the art can be used.

[0053] In a preferred embodiment of the present invention, the original material of the above-mentioned manganese-based composite positive electrode material is further subjected to surface modification treatment by using technical means well known to those skilled in the art, and the present invention has no special limitation on this.

[0054] In the present invention, the temperature of the first coprecipitation reaction is preferably 50° C. to 60° C., the stirring speed is preferably 400 r / min to 1000 r / min, the pH value is preferably 7.5 to 11.5, and the time is preferably 40 h to 120 h.

[0055] In the present invention, the temperature of the second coprecipitation reaction is preferably 40° C. to 60° C., the stirring speed is preferably 700 r / min to 900 r / min, the pH value is preferably 7.9 to 11.9, and the time is preferably 10 h to 20 h.

[0056] In the present invention, the pre-oxidation temperature is preferably 300° C. to 600° C., and the pre-oxidation time is preferably 4 h to 16 h.

[0057] In the present invention, the sintering temperature is preferably 800° C. to 1200° C., and the sintering time is preferably 10 h to 25 h.

[0058] The present invention adopts a coprecipitation method to prepare in situ a manganese-based composite positive electrode material precursor with a core mainly manganese and a shell mainly nickel-cobalt-manganese, and then after pre-oxidation, lithium mixing, and sintering modification, a manganese-based composite positive electrode material with a core of lithium manganate material and a shell of lithium-rich manganese-based positive electrode material is obtained. The high-capacity, high-safety, long-cycle, and high-density manganese-based composite positive electrode material solves the cycle stability and high-temperature storage problems of manganese-based positive electrode materials; further, the manganese-based composite positive electrode material is used as a lithium ion battery positive electrode material, and a lithium ion battery with high energy density, long life, and high safety can be prepared. At the same time, the preparation method provided by the present invention has a simple process, easy-to-control conditions, and has broad application prospects.

[0059] The present invention also provides a positive electrode sheet, comprising the manganese-based composite positive electrode material described in the above technical solution. In the present invention, the manganese-based composite positive electrode material has a core-shell structure with a lithium manganese oxide core and a lithium-rich manganese-based shell, which can play a lithium supplement role in the battery, improve the cycle stability and manganese dissolution problem of the manganese-based material, and achieve the long cycle, high safety, and high compaction effect of the low-cost composite manganese-based positive electrode material battery.

[0060] The present invention has no special restrictions on the preparation process of the positive electrode sheet, and any technical means for preparing the positive electrode sheet known to those skilled in the art can be used.

[0061] The present invention also provides a lithium-ion battery, which uses the positive electrode sheet described in the above technical solution as a positive electrode.

[0062] In the present invention, the above-mentioned manganese-based composite positive electrode material is assembled with one or more of negative electrode materials such as graphite, artificial graphite, silicon-carbon material, lithium metal negative electrode, lithium carbon negative electrode material, and a separator into a high-energy lithium-ion battery; the lithium-ion battery can operate in any high voltage range of 4.35V-4.8V after being activated above 4.35V in the first cycle.

[0063] The present invention provides a manganese-based composite positive electrode material and a preparation method and application thereof; the manganese-based composite positive electrode material has a core-shell structure; the core of the core-shell structure is a lithium manganate material, and the shell is a lithium-rich manganese-based positive electrode material. Compared with the prior art, the present invention adopts a coprecipitation method to in-situ prepare a manganese-based composite positive electrode material precursor with a core mainly composed of manganese and a shell mainly composed of nickel, cobalt and manganese, and then obtains a high-capacity, high-safety, long-cycle, high-density manganese-based composite positive electrode material with a core of lithium manganate material and a shell of lithium-rich manganese-based positive electrode material after pre-oxidation, lithium mixing, and sintering modification, thereby solving the problems of cycle stability and high-temperature storage of manganese-based positive electrode materials; further adopting the manganese-based composite positive electrode material as a lithium-ion battery positive electrode material can prepare a lithium-ion battery with high energy density, long life and high safety.

[0064] At the same time, the preparation method provided by the present invention has simple process, easily controllable conditions and broad application prospects.

[0065] In order to further illustrate the present invention, the following examples are provided for detailed description. The reagents used in the following examples of the present invention are all commercially available.

[0066] Example 1

[0067] Preparation of manganese-based composite positive electrode materials:

[0068] (1) A manganese sulfate compound is mixed with water to obtain 5 L of a 2 mol / L manganese sulfate salt solution containing manganese; sodium carbonate powder is mixed with the aqueous solution to obtain a 2 mol / L sodium carbonate solution as a precipitant; and a 25% ammonia solution is diluted to a 0.2 mol / L ammonia solution as a complexing agent.

[0069] (2) The manganese sulfate solution was added to the coprecipitation reactor at a rate of 2 mL / min and the complexing agent was added at a rate of 0.5 mL / min by a metering pump. At the same time, the reaction pH was controlled to be between 7.8±0.05 by adding sodium carbonate solution. The temperature of the reactor was controlled to be 55°C and the stirring speed was 500 r / min. After the coprecipitation reaction was carried out for 42 hours, a spherical manganese oxide material precursor MnCO3 suspension containing primary particles of 100 nm and secondary particles with a particle size D50 of 8 μm was obtained.

[0070] (3) Nickel sulfate, cobalt sulfate and manganese sulfate compounds are prepared in a ratio of 1:1:4 to prepare 0.5 L of a 2 mol / L mixed solution.

[0071] (4) The mixed salt solution prepared in (3) and the 2 mol / L precipitant sodium carbonate solution and the 0.2 mol / L ammonia solution of the complexing agent described in (1) are added to the coprecipitation reactor containing the spherical manganese oxide material precursor suspension obtained in (2) through a metering pump. The reactor temperature is controlled at 55° C., the stirring speed is 800 r / min, and the reaction pH value is between 7.9±0.05. After the coprecipitation reaction is carried out for 15 hours, a spherical MnCO3 material containing a core and a Ni outer shell is obtained. 0.167 Co 0.167 Mn 0.666 The secondary particle size D50 of CO3 material is 8.5μm. The manganese-based composite material precursor of the spherical nickel-cobalt-manganese multi-material precursor is 0.9MnCO3-0.1Ni 0.167 Co 0.167 Mn 0.666 CO3 suspension.

[0072] (5) Washing, filtering and drying the composite material precursor suspension to obtain a composite material precursor.

[0073] (6) The composite material precursor was pre-oxidized at 350 °C for 5 h to obtain 0.9Mn3O4-0.1[Ni0.167 Co 0.167 Mn 0.666 ]3O4 composite manganese-based positive electrode material precursor oxide.

[0074] (7) The above-mentioned composite manganese-based positive electrode material precursor oxide and lithium carbonate are solid-phase mixed according to the molar ratio of lithium to transition metal Li:Me=1:1.86, and sintered at 875°C for 12h to obtain a secondary spherical LiMn2O4 with a core and a Li 1.2 Ni 0.133 Co 0.133 Mn 0.544 O2 secondary ball manganese-based composite cathode material 0.9LiMn2O4-0.1Li 1.2 Ni 0.133 Co 0.133 Mn 0.544 The raw materials of O2, the preparation flow chart is shown in Figure 1 As shown, SEM see Figure 2 As shown, it can be seen from the schematic diagram that a positive electrode material with a core of polycrystalline lithium manganese oxide and a shell of polycrystalline lithium-rich manganese-based positive electrode material is prepared.

[0075] (8) The original material of the above-mentioned manganese-based composite positive electrode material is subjected to surface aluminum oxide coating to obtain 0.9LiMn2O4-0.1Li 1.2 Ni 0.133 Co 0.133 Mn 0.544 O2 manganese-based composite positive electrode material.

[0076] Preparation of positive electrode:

[0077] (9) The above-mentioned manganese-based composite positive electrode material is added with 3.5% conductive agent SP+carbon nanotubes (mass ratio 6:1), 1.5% binder PVDF, and solvent NMP at a mass ratio of 5% of the positive electrode material into a mixing kettle and stirred to obtain a lithium-ion battery composite positive electrode material slurry.

[0078] (10) The composite positive electrode material slurry is coated on the positive electrode current collector, and the positive electrode material electrode sheet is obtained by drying, slicing and rolling.

[0079] Preparation of negative electrode sheet:

[0080] (11) Similarly, the negative electrode active material graphite negative electrode material with a discharge capacity of 350 mAh / g, the conductive agent SP, the binder CMC, and the solvent SBR are added into a mixing kettle in a ratio of 93.5:1.5:1:4 and stirred to obtain a lithium ion battery negative electrode material slurry.

[0081] (12) The negative electrode material slurry is coated on the positive electrode current collector, and the electrode sheet is dried, sliced, and rolled to obtain the negative electrode material electrode sheet for standby use.

[0082] Preparation of the battery:

[0083] (13) Assemble the above positive and negative electrode sheets into a 25Ah battery cell by stacking them.

[0084] (14) The above-mentioned battery cell is baked, injected with electrolyte, and formed to obtain a lithium-ion battery.

[0085] Battery Test:

[0086] (15) The battery is charged to above 4.35V for the first cycle and then activated and cycled within a voltage range of 2V to 4.35V.

[0087] After testing, the tap density of the above material reaches 2.0g / cc, and the material's first cycle discharge capacity reaches 135mAh / g in the voltage range of 2V to 4.35V for the half-cell. The compaction density of the positive electrode sheet prepared in the above step (8) is as high as 2.9g / cc, and the first efficiency of the assembled full battery reaches 93%, and the capacity retention rate of the full battery after 1500 cycles in the voltage range of 2.8V to 4.35V is 92%. It is suitable for the basic needs of low-cost long-cycle power battery applications.

[0088] Example 2

[0089] Preparation of manganese-based composite positive electrode materials:

[0090] (1) A manganese sulfate compound is mixed with water to obtain 5 L of a 2 mol / L manganese sulfate salt solution containing manganese; sodium hydroxide is mixed with the aqueous solution to obtain a 4 mol / L sodium hydroxide solution as a precipitant; and a 25% ammonia solution is diluted to a 1.0 mol / L ammonia solution as a complexing agent.

[0091] (2) The manganese sulfate solution was added to a coprecipitation reactor protected by a nitrogen atmosphere at a rate of 1 mL / min and the complexing agent was added at a rate of 0.8 mL / min by a metering pump. At the same time, the reaction pH was controlled to be between 9.5±0.05 by adding sodium hydroxide solution. The reactor temperature was controlled at 55°C and the stirring speed was 500 r / min. After the coprecipitation reaction was carried out for 83 hours, a spherical manganese oxide material precursor Mn(OH)2 suspension containing primary particles of 400 nm and secondary particles with a particle size D50 of 6 μm was obtained.

[0092] (3) Nickel sulfate, cobalt sulfate and manganese sulfate compounds are prepared in a ratio of 1:1:4 to prepare 0.5 L of a 2 mol / L mixed solution.

[0093] (4) The mixed salt solution prepared in step (3) and 8 mol / L sodium hydroxide solution as a precipitant and 1.2 mol / L ammonia solution as a complexing agent were added into the coprecipitation reactor containing the spherical manganese oxide material precursor suspension obtained in step (2) and protected by a nitrogen atmosphere by controlling the reactor temperature at 45°C, the stirring speed at 800 r / min, and the reaction pH at 9.9±0.05. After the coprecipitation reaction was carried out for 15 hours, a spherical Mn(OH)2 material containing a core and a Ni outer shell was obtained. 0.167 Co 0.167 Mn 0.666 The secondary particle size D50 of (OH)2 material is 6.2μm, and the manganese-based composite material precursor of nickel-cobalt-manganese multi-material precursor is 0.9Mn(OH)2-0.1Ni 0.167 Co 0.167 Mn 0.666 (OH)2 suspension.

[0094] (5) Washing, filtering and drying the composite material precursor suspension to obtain a composite material precursor.

[0095] (6) The composite material precursor was pre-oxidized at 320 °C for 10 h to obtain 0.9Mn3O4-0.1[Ni 0.167 Co 0.167 Mn 0.666 ]3O4 composite manganese-based positive electrode material precursor oxide.

[0096] (7) The above composite manganese-based positive electrode material precursor oxide and lithium hydroxide are solid-phase mixed according to the molar ratio of lithium to transition metal Li:Me=1:1.86, and sintered at 805°C for 16h to obtain secondary spheres with LiMn2O4 as the inner core and Li as the outer shell. 1.2 Ni 0.133 Co 0.133 Mn 0.544 O2 secondary ball manganese-based composite cathode material 0.9LiMn2O4-0.1Li 1.2 Ni 0.133 Co 0.133 Mn 0.544 O2's original material.

[0097] (8) The original material of the above-mentioned manganese-based composite positive electrode material is subjected to surface alumina coating to obtain 0.9LiMn2O-0.1Li 1.2 Ni 0.133 Co 0.133 Mn 0.544 O2 manganese-based composite positive electrode material.

[0098] Preparation of positive electrode:

[0099] (9) The above-mentioned manganese-based composite positive electrode material is added with 3.5% conductive agent SP+carbon nanotubes (mass ratio 6:1), 1.5% binder PVDF, and solvent NMP at a mass ratio of 5% of the positive electrode material into a mixing kettle and stirred to obtain a lithium-ion battery composite positive electrode material slurry.

[0100] (10) The composite positive electrode material slurry is coated on the positive electrode current collector, and the positive electrode material electrode sheet is obtained by drying, slicing and rolling.

[0101] Preparation of negative electrode sheet:

[0102] (11) Similarly, the negative electrode active material graphite negative electrode material with a discharge capacity of 350 mAh / g, the conductive agent SP, the binder CMC, and the solvent SBR are added into a mixing kettle in a ratio of 93.5:1.5:1:4 and stirred to obtain a lithium ion battery negative electrode material slurry.

[0103] (12) The negative electrode material slurry is coated on the positive electrode current collector, and the electrode sheet is dried, sliced, and rolled to obtain the negative electrode material electrode sheet for standby use.

[0104] Preparation of the battery:

[0105] (13) Assemble the above positive and negative electrode sheets into a 25Ah battery cell by stacking.

[0106] (14) The above-mentioned battery cell is baked, injected with electrolyte, and formed to obtain a lithium-ion battery.

[0107] Battery Test:

[0108] (15) The battery is charged to above 4.35V for the first cycle and then activated and cycled within a voltage range of 2V to 4.35V.

[0109] After testing, the tap density of the above material reaches 2.2g / cc, and the material's first cycle discharge capacity reaches 130mAh / g in the voltage range of 2V to 4.35V for the half-cell. The compaction density of the positive electrode sheet prepared in the above step (8) is as high as 3.1g / cc, and the first efficiency of the assembled full battery reaches 93%, and the capacity retention rate of the full battery after 2500 cycles in the voltage range of 2.8V to 4.35V is 92%. It is suitable for the basic needs of low-cost long-cycle power battery applications.

[0110] Example 3

[0111] Preparation of manganese-based composite positive electrode materials:

[0112] (1) A manganese sulfate compound is mixed with water to obtain 10 L of a 2 mol / L manganese sulfate salt solution containing manganese; sodium carbonate powder is mixed with the aqueous solution to obtain a 2 mol / L sodium carbonate solution as a precipitant; and a 25% ammonia solution is diluted to a 0.2 mol / L ammonia solution as a complexing agent.

[0113] (2) The manganese sulfate solution was added to the coprecipitation reactor at a rate of 6 mL / min and the complexing agent was added at a rate of 0.5 mL / min by a metering pump, and the reaction pH was controlled to be between 7.8±0.05 by adding sodium carbonate solution. The temperature of the reactor was controlled at 55°C and the stirring speed was 500 r / min. After the coprecipitation reaction was carried out for 42 hours, a spherical manganese oxide material precursor MnCO3 suspension containing primary particles of 100 nm and secondary particles with a particle size D50 of 10 μm was obtained.

[0114] (3) Nickel sulfate, cobalt sulfate and manganese sulfate compounds are prepared in a ratio of 1:1:8 to prepare 0.5 L of a 2 mol / L mixed solution.

[0115] (4) The mixed salt solution prepared in (3) and the 2 mol / L sodium carbonate solution as a precipitant and the 0.2 mol / L ammonia solution as a complexing agent described in (1) are added into the coprecipitation reactor containing the spherical manganese oxide material precursor suspension obtained in step (2) by a metering pump. The reactor temperature is controlled at 50° C., the stirring speed is 800 r / min, and the reaction pH value is between 8.2±0.05. After the coprecipitation reaction is carried out for 15 hours, a spherical MnCO3 material containing a core and a Ni outer shell is obtained. 0.1 Co 0.1 Mn 0.8 The secondary particle size D50 of CO3 material is 10.5μm. The manganese-based composite material precursor of nickel-cobalt-manganese multi-material precursor is 0.95MnCO3-0.05Ni 0.1 Co 0.1 Mn 0.8 CO3 suspension.

[0116] (5) Washing, filtering and drying the composite material precursor suspension to obtain a composite material precursor.

[0117] (6) The composite material precursor was pre-oxidized at 350 °C for 5 h to obtain 0.95Mn3O4-0.05[Ni 0.1 Co 0.1 Mn 0.8 ]3O4 composite manganese-based positive electrode material precursor oxide.

[0118] (7) The above composite manganese-based positive electrode material precursor oxide and lithium carbonate were solid-phase mixed according to the molar ratio of lithium to transition metal Li:Me=1:1.9, and then subjected to 895°C for 16h to obtain a LiMn2O4 core and a Li 1.4 Ni 0.08 Co 0.08 Mn 0.64 O2 manganese-based composite cathode material 0.95LiMn2O4-0.05Li 1.4 Ni 0.08 Co 0.08 Mn 0.64 O2's original material.

[0119] (8) The original material of the above-mentioned manganese-based composite positive electrode material is subjected to surface modification to obtain 0.95LiMn2O4-0.05Li 1.4 Ni 0.08 Co 0.08 Mn 0.64 O2 manganese-based composite positive electrode material.

[0120] Preparation of positive electrode:

[0121] (9) The above-mentioned manganese-based composite positive electrode material is added with 3.5% conductive agent SP+carbon nanotubes (mass ratio 6:1), 1.5% binder PVDF, and solvent NMP at a mass ratio of 5% of the positive electrode material into a mixing kettle and stirred to obtain a lithium-ion battery composite positive electrode material slurry.

[0122] (10) The composite positive electrode material slurry is coated on the positive electrode current collector, and the positive electrode material electrode sheet is obtained by drying, slicing and rolling.

[0123] Preparation of negative electrode sheet:

[0124] (11) Similarly, the negative electrode active material graphite negative electrode material with a discharge capacity of 350 mAh / g, the conductive agent SP, the binder CMC, and the solvent SBR are added into a mixing kettle in a ratio of 93.5:1.5:1:4 and stirred to obtain a lithium ion battery negative electrode material slurry.

[0125] (12) The negative electrode material slurry is coated on the positive electrode current collector, and the electrode sheet is dried, sliced, and rolled to obtain the negative electrode material electrode sheet for standby use.

[0126] Preparation of the battery:

[0127] (13) The positive and negative electrode sheets are assembled into a 25Ah battery cell by winding.

[0128] (14) The above-mentioned battery cell is baked, injected with electrolyte, and formed to obtain a lithium-ion battery.

[0129] Battery Test:

[0130] (15) The battery is charged to above 4.35V in the first cycle and then activated and cycled within a voltage range of 2V to 4.35V.

[0131] After testing, the tap density of the above material reaches 2.1g / cc, and the material's first cycle discharge capacity reaches 132mAh / g in the voltage range of 2V to 4.35V for the half-cell. The compaction density of the positive electrode sheet prepared in the above step (8) is as high as 2.92g / cc, and the first efficiency of the assembled full battery reaches 92%, and the capacity retention rate of the full battery is 91% after 1500 cycles in the voltage range of 2.8V to 4.35V. It is suitable for the basic needs of low cost and long cycle.

[0132] Example 4

[0133] Preparation of manganese-based composite positive electrode materials:

[0134] (1) A manganese sulfate compound is mixed with water to obtain 5 L of a 2 mol / L manganese sulfate salt solution containing manganese; sodium hydroxide is mixed with the aqueous solution to obtain a 4 mol / L sodium hydroxide solution as a precipitant; and a 25% ammonia solution is diluted to a 1.0 mol / L ammonia solution as a complexing agent.

[0135] (2) The manganese sulfate solution was added to a coprecipitation reactor protected by a nitrogen atmosphere at a rate of 1 mL / min and the complexing agent was added at a rate of 0.8 mL / min by a metering pump. At the same time, the reaction pH was controlled to be between 10.7±0.05 by adding sodium hydroxide solution. The reactor temperature was controlled at 55°C and the stirring speed was 900 r / min. After the coprecipitation reaction was carried out for 120 hours, a spherical manganese oxide material precursor Mn(OH)2 suspension containing primary particles of 400 nm and secondary particles with a particle size D50 of 4 μm was obtained.

[0136] (3) Nickel sulfate, cobalt sulfate and manganese sulfate compounds are prepared in a ratio of 1:1:4 to prepare 0.5 L of a 2 mol / L mixed solution.

[0137] (4) The mixed salt solution prepared in step (3) and 8 mol / L sodium hydroxide solution as a precipitant and 1.2 mol / L ammonia solution as a complexing agent were added into the coprecipitation reactor containing the spherical manganese oxide material precursor suspension obtained in step (2) and protected by a nitrogen atmosphere. The reactor temperature was controlled at 45°C, the stirring speed was 800 r / min, and the reaction pH value was between 11.0±0.05. After the coprecipitation reaction was carried out for 15 hours, a spherical Mn(OH)2 material containing a core and a Ni outer shell was obtained. 0.167 Co 0.167 Mn 0.666The secondary particle size D50 of (OH)2 material is 4.2μm, and the manganese-based composite material precursor of nickel-cobalt-manganese multi-material precursor is 0.9Mn(OH)2-0.1Ni 0.167 Co 0.167 Mn 0.666 (OH)2 suspension.

[0138] (5) The composite material precursor suspension is washed, filtered and dried to obtain a composite material precursor.

[0139] (6) The composite precursor was pre-oxidized at 520 °C for 10 h to obtain 0.9Mn3O4-0.1[Ni 0.167 Co 0.167 Mn 0.666 ]3O4 composite manganese-based positive electrode material precursor oxide.

[0140] (7) The above-mentioned composite manganese-based positive electrode material precursor oxide and lithium hydroxide are solid-phase mixed according to the molar ratio of lithium to transition metal Li:Me=1:1.9, and sintered at 1050°C for 12h to obtain LiMn2O4 with a single crystal core and a secondary spherical shell. 1.2 Ni 0.133 Co 0.133 Mn 0.544 O2 manganese-based composite cathode material 0.9LiMn2O4-0.1Li 1.2 Ni 0.133 Co 0.133 Mn 0.544 Original material of O2, SEM see Figure 3 As shown, it can be seen from the schematic diagram that a positive electrode material with a core of multiple single-crystal lithium manganese oxide and a shell of polycrystalline lithium-rich manganese-based positive electrode material is prepared.

[0141] (8) The original material of the composite cathode material was surface modified to obtain 0.9LiMn2O4-0.1Li 1.2 Ni 0.133 Co 0.133 Mn 0.544 O2 manganese-based composite positive electrode material.

[0142] Preparation of positive electrode:

[0143] (9) The above-mentioned manganese-based composite positive electrode material is added with 3.5% conductive agent SP+carbon nanotubes (mass ratio 6:1), 1.5% binder PVDF, and solvent NMP at a mass ratio of 5% of the positive electrode material into a mixing kettle and stirred to obtain a lithium-ion battery composite positive electrode material slurry.

[0144] (10) The composite positive electrode material slurry is coated on the positive electrode current collector, and the positive electrode material electrode sheet is obtained by drying, slicing and rolling.

[0145] Preparation of negative electrode sheet:

[0146] (11) Similarly, the negative electrode active material graphite negative electrode material with a discharge capacity of 350 mAh / g, the conductive agent SP, the binder CMC, and the solvent SBR are added into a mixing kettle in a ratio of 93.5:1.5:1:4 and stirred to obtain a lithium ion battery negative electrode material slurry.

[0147] (12) The negative electrode material slurry is coated on the positive electrode current collector, and the electrode sheet is dried, sliced, and rolled to obtain the negative electrode material electrode sheet for standby use.

[0148] Preparation of the battery:

[0149] (13) Assemble the above positive and negative electrode sheets into a 25Ah battery cell by stacking.

[0150] (14) The above-mentioned battery cell is baked, injected with electrolyte, and formed to obtain a lithium-ion battery.

[0151] Battery Test:

[0152] (15) The battery is charged to above 4.35V for the first cycle and then activated and cycled within a voltage range of 2V to 4.35V.

[0153] After testing, the tap density of the above material reaches 2.2g / cc, and the material's first cycle discharge capacity reaches 121mAh / g in the voltage range of 2V to 4.35V for the half-cell. The compaction density of the positive electrode sheet prepared in the above step (8) is as high as 3.2g / cc, and the first efficiency of the assembled full battery reaches 92%, and the capacity retention rate of the full battery is 94% after 2500 cycles in the voltage range of 2.8V to 4.35V. It is suitable for the basic needs of low-cost long-cycle power battery applications.

[0154] Example 5

[0155] Preparation of manganese-based composite positive electrode materials:

[0156] (1) A manganese sulfate compound is mixed with water to obtain 5 L of a 2 mol / L manganese sulfate salt solution containing manganese; sodium hydroxide is mixed with the aqueous solution to obtain a 4 mol / L sodium hydroxide solution as a precipitant; and a 25% ammonia solution is diluted to a 1.0 mol / L ammonia solution as a complexing agent.

[0157] (2) The manganese sulfate solution was added to a coprecipitation reactor protected by a nitrogen atmosphere at a rate of 1 mL / min and the complexing agent was added at a rate of 0.8 mL / min by a metering pump. At the same time, the reaction pH was controlled to be between 10.5±0.05 by adding sodium hydroxide solution. The reactor temperature was controlled at 55°C and the stirring speed was 900 r / min. After the coprecipitation reaction was carried out for 120 hours, a spherical manganese oxide material precursor Mn(OH)2 suspension containing primary particles of 400 nm and secondary particles with a particle size D50 of 4 μm was obtained.

[0158] (3) Nickel sulfate, cobalt sulfate and manganese sulfate compounds are prepared in a ratio of 1:1:4 to prepare 0.5 L of a 2 mol / L mixed solution.

[0159] (4) The mixed salt solution prepared in step (3) and 8 mol / L sodium hydroxide solution as a precipitant and 1.2 mol / L ammonia solution as a complexing agent were added into the coprecipitation reactor containing the spherical manganese oxide material precursor suspension obtained in step (2) and protected by a nitrogen atmosphere by controlling the reactor temperature at 45°C, the stirring speed at 800 r / min, and the reaction pH at 9.9±0.05. After the coprecipitation reaction was carried out for 15 hours, a spherical Mn(OH)2 material containing a core and a Ni outer shell was obtained. 0.167 Co 0.167 Mn 0.666 The secondary particle size D50 of (OH)2 material is 4.2μm, and the manganese-based composite material precursor of nickel-cobalt-manganese multi-material precursor is 0.9Mn(OH)2-0.1Ni 0.167 Co 0.167 Mn 0.666 (OH)2 suspension.

[0160] (5) The composite material precursor suspension is washed, filtered and dried to obtain a composite material precursor.

[0161] (6) The composite precursor was pre-oxidized at 520 °C for 10 h to obtain 0.9Mn3O4-0.1[Ni 0.167 Co 0.167 Mn 0.666 ]3O4 composite manganese-based positive electrode material precursor oxide.

[0162] (7) The above-mentioned composite manganese-based positive electrode material precursor oxide and lithium hydroxide are solid-phase mixed according to the molar ratio of lithium to transition metal Li:Me=1:1.9, and 5% by mass of boric acid as a solvent is added, and sintered at 1150°C for 10 hours to obtain LiMn2O4 with a single crystal morphology as the inner core and a single crystal Li as the outer shell. 1.2 Ni 0.133 Co 0.133 Mn 0.544O2 manganese-based composite cathode material 0.9LiMn2O4-0.1Li 1.2 Ni 0.133 Co 0.133 Mn 0.544 Original material of O2, SEM see Figure 5 As shown, it can be seen from the schematic diagram that a positive electrode material with a core of a single single crystal lithium manganese oxide and an outer shell of multiple single crystals rich in lithium manganese is prepared.

[0163] (8) The original material of the composite cathode material was surface modified to obtain 0.9LiMn2O4-0.1Li 1.2 Ni 0.133 Co 0.133 Mn 0.544 O2 manganese-based composite positive electrode material.

[0164] Preparation of positive electrode:

[0165] (9) The above-mentioned manganese-based composite positive electrode material is added with 3.5% conductive agent SP+carbon nanotubes (mass ratio 6:1), 1.5% binder PVDF, and solvent NMP at a mass ratio of 5% of the positive electrode material into a mixing kettle and stirred to obtain a lithium-ion battery composite positive electrode material slurry.

[0166] (10) The composite positive electrode material slurry is coated on the positive electrode current collector, and the positive electrode material electrode sheet is obtained by drying, slicing and rolling.

[0167] Preparation of negative electrode sheet:

[0168] (11) Similarly, the negative electrode active material graphite negative electrode material with a discharge capacity of 350 mAh / g, the conductive agent SP, the binder CMC, and the solvent SBR are added into a mixing kettle in a ratio of 93.5:1.5:1:4 and stirred to obtain a lithium ion battery negative electrode material slurry.

[0169] (12) The negative electrode material slurry is coated on the positive electrode current collector, and the electrode sheet is dried, sliced, and rolled to obtain the negative electrode material electrode sheet for standby use.

[0170] Preparation of the battery:

[0171] (13) Assemble the above positive and negative electrode sheets into a 25Ah battery cell by stacking.

[0172] (14) The above-mentioned battery cell is baked, injected with electrolyte, and formed to obtain a lithium-ion battery.

[0173] Battery Test:

[0174] (15) The battery is charged to above 4.35V for the first cycle and then activated and cycled within a voltage range of 2V to 4.35V.

[0175] After testing, the tap density of the above material reaches 2.2g / cc, and the material's first cycle discharge capacity reaches 135mAh / g in the voltage range of 2V to 4.45V for the half-cell. The compaction density of the positive electrode sheet prepared in the above step (8) is as high as 3.2g / cc, and the first efficiency of the assembled full battery reaches 92.5%, and the capacity retention rate of the full battery is 95% after 2500 cycles in the voltage range of 2.8V to 4.35V. It is suitable for the basic needs of low-cost long-cycle power battery applications.

[0176] Example 6

[0177] Preparation of manganese-based composite positive electrode materials:

[0178] (1) A manganese sulfate compound is mixed with water to obtain 5 L of a 2 mol / L manganese sulfate salt solution containing manganese; sodium hydroxide is mixed with the aqueous solution to obtain a 4 mol / L sodium hydroxide solution as a precipitant; and a 25% ammonia solution is diluted to a 1.0 mol / L ammonia solution as a complexing agent.

[0179] (2) The manganese sulfate solution was added to a coprecipitation reactor protected by a nitrogen atmosphere at a rate of 1 mL / min and the complexing agent was added at a rate of 0.8 mL / min by a metering pump. At the same time, the reaction pH was controlled to be between 10.5±0.05 by adding sodium hydroxide solution. The reactor temperature was controlled at 55°C and the stirring speed was 900 r / min. After the coprecipitation reaction was carried out for 120 hours, a spherical manganese oxide material precursor Mn(OH)2 suspension containing primary particles of 400 nm and secondary particles with a particle size D50 of 4 μm was obtained.

[0180] (3) Nickel sulfate, cobalt sulfate and manganese sulfate compounds are prepared in a ratio of 1:1:4 to prepare 0.5 L of a 2 mol / L mixed solution.

[0181] (4) The mixed salt solution prepared in step (3) and 8 mol / L sodium hydroxide solution as a precipitant and 1.2 mol / L ammonia solution as a complexing agent were added into the coprecipitation reactor containing the spherical manganese oxide material precursor suspension obtained in step (2) and protected by a nitrogen atmosphere by controlling the reactor temperature at 45°C, the stirring speed at 800 r / min, and the reaction pH at 9.9±0.05. After the coprecipitation reaction was carried out for 15 hours, a spherical Mn(OH)2 material containing a core and a Ni outer shell was obtained. 0.167 Co 0.167 Mn 0.666 The secondary particle size D50 of (OH)2 material is 4.2μm, and the manganese-based composite material precursor of nickel-cobalt-manganese multi-material precursor is 0.9Mn(OH)2-0.1Ni 0.167 Co 0.167 Mn 0.666 (OH)2 suspension.

[0182] (5) The composite material precursor suspension is washed, filtered and dried to obtain a composite material precursor.

[0183] (6) The composite material precursor was pre-oxidized at 520 °C for 10 h to obtain 0.9Mn3O4-0.1[Ni 0.167 Co 0.167 Mn 0.666 ]3O4 composite manganese-based positive electrode material precursor oxide.

[0184] (7) The above-mentioned composite manganese-based positive electrode material precursor oxide and lithium hydroxide are solid-phase mixed according to the molar ratio of lithium to transition metal Li:Me=1:1.9, and 5% by mass of boric acid as a solvent is added, and sintered at 1150°C for 12h to obtain LiMn2O4 with a core of 4 single crystals and a shell of single crystal Li 1.2 Ni 0.133 Co 0.133 Mn 0.544 O2 manganese-based composite cathode material 0.9LiMn2O4-0.1Li 1.2 Ni 0.133 Co 0.133 Mn 0.544 Original material of O2, SEM see Figure 4 As shown, it can be seen from the schematic diagram that a positive electrode material having a core of multiple single-crystal lithium manganese oxides and an outer shell of multiple single-crystal lithium-rich manganese-based positive electrode materials is prepared.

[0185] (8) The original material of the composite cathode material was surface modified to obtain 0.9LiMn2O4-0.1Li 1.2 Ni 0.133 Co 0.133 Mn 0.544 O2 manganese-based composite positive electrode material.

[0186] Preparation of positive electrode:

[0187] (9) The above-mentioned manganese-based composite positive electrode material is added with 3.5% conductive agent SP+carbon nanotubes (mass ratio 6:1), 1.5% binder PVDF, and solvent NMP at a mass ratio of 5% of the positive electrode material into a mixing kettle and stirred to obtain a lithium-ion battery composite positive electrode material slurry.

[0188] (10) The composite positive electrode material slurry is coated on the positive electrode current collector, and the positive electrode material electrode sheet is obtained by drying, slicing and rolling.

[0189] Preparation of negative electrode sheet:

[0190] (11) Similarly, the negative electrode active material graphite negative electrode material with a discharge capacity of 350 mAh / g, the conductive agent SP, the binder CMC, and the solvent SBR are added into a mixing kettle in a ratio of 93.5:1.5:1:4 and stirred to obtain a lithium ion battery negative electrode material slurry.

[0191] (12) The negative electrode material slurry is coated on the positive electrode current collector, and the electrode sheet is dried, sliced, and rolled to obtain the negative electrode material electrode sheet for standby use.

[0192] Preparation of the battery:

[0193] (13) Assemble the above positive and negative electrode sheets into a 25Ah battery cell by stacking.

[0194] (14) The above-mentioned battery cell is baked, injected with electrolyte, and formed to obtain a lithium-ion battery.

[0195] Battery Test:

[0196] (15) The battery is charged to above 4.35V for the first cycle and then activated and cycled within a voltage range of 2 to 4.35V.

[0197] After testing, the tap density of the above material reaches 2.2g / cc, and the material's first cycle discharge capacity reaches 140mAh / g in the voltage range of 2V to 4.45V for the half-cell. The compaction density of the positive electrode sheet prepared in the above step (8) is as high as 3.2g / cc, and the first efficiency of the assembled full battery reaches 92.5%, and the capacity retention rate of the full battery is 95% after 2500 cycles in the voltage range of 2.8V to 4.35V. It is suitable for the basic needs of low-cost long-cycle power battery applications.

[0198] In summary, the present invention provides a manganese-based composite positive electrode material and its preparation method and application; the manganese-based composite positive electrode material has a core-shell structure with a core of lithium manganese oxide and a shell layer of lithium-rich manganese, which can play a role in lithium supplementation in the battery, improve the cycle stability and manganese dissolution problem of manganese-based materials, and achieve the long cycle, high safety, and high compaction effect of low-cost composite manganese-based positive electrode material batteries. Compared with the prior art, the preparation method of the manganese-based composite positive electrode material provided by the present invention adopts a coprecipitation method to synthesize a core of manganese-based and a shell of nickel, cobalt, and manganese-based in-situ growth precipitation to prepare a manganese-based composite positive electrode material precursor, and then obtains a high-capacity, high-safety, long-cycle, and high-compacted manganese-based composite positive electrode material with a core of lithium manganese oxide and a shell of lithium-rich manganese-based positive electrode material after pre-oxidation, lithium mixing, and sintering modification; the above-mentioned manganese-based composite positive electrode material is further used as a lithium-ion battery positive electrode material to prepare a lithium-ion battery with high energy density, long life, and high safety.

[0199] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A manganese-based composite positive electrode material, characterized in that: It has a core-shell structure; The core of the core-shell structure is a lithium manganese oxide material, and the shell is a lithium-rich manganese-based positive electrode material.

2. The manganese-based composite positive electrode material according to claim 1, characterized in that: The general formula of the manganese-based composite positive electrode material is (1-x)LiMn2O4-xLi 1+y Ni a Co b Mn c O2; Among them, 0<x≤0.15, y>0, 0<a<0.5, 0≤b<0.5, 0<c<1.

3. The manganese-based composite positive electrode material according to claim 1, characterized in that: The inner core is polycrystalline lithium manganese oxide, multiple single-crystal lithium manganese oxide or single single-crystal lithium manganese oxide; the outer shell is polycrystalline lithium-rich manganese-based positive electrode material or multiple single-crystal lithium-rich manganese-based positive electrode materials.

4. The manganese-based composite positive electrode material according to claim 1, characterized in that: The diameter of the inner core is 1 μm to 15 μm; the thickness of the outer shell is 50 nm to 500 nm; and the diameter of the core-shell structure is 1 μm to 16 μm.

5. A method for preparing the manganese-based composite positive electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: a) mixing a manganese-containing salt solution, a precipitant, and a complexing agent to perform a first coprecipitation reaction to obtain a precursor suspension containing a spherical manganese oxide material; b) adding a mixed solution containing nickel, cobalt and manganese, a precipitant and a complexing agent to the precursor suspension containing the spherical manganese oxide material obtained in step a), and performing a second coprecipitation reaction to obtain a manganese-based composite material precursor suspension; c) washing, filtering and drying the manganese-based composite material precursor suspension obtained in step b) to obtain a composite material precursor; d) pre-oxidizing the composite material precursor obtained in step c) to obtain a precursor oxide; e) solid-phase mixing the precursor oxide obtained in step d) with a lithium source and then sintering to obtain a manganese-based composite positive electrode material.

6. The preparation method according to claim 5, characterized in that: The temperature of the first coprecipitation reaction in step a) is 50° C. to 60° C., the stirring speed is 400 r / min to 1000 r / min, the pH value is 7.5 to 11.5, and the time is 40 h to 120 h.

7. The preparation method according to claim 5, characterized in that: The temperature of the second coprecipitation reaction in step b) is 40° C. to 60° C., the stirring speed is 700 r / min to 900 r / min, the pH value is 7.9 to 11.9, and the time is 10 h to 20 h.

8. The preparation method according to claim 5, characterized in that: The sintering temperature in step e) is 800° C. to 1200° C., and the sintering time is 10 h to 25 h.

9. A positive electrode sheet, characterized in that: It comprises the manganese-based composite positive electrode material as described in any one of claims 1 to 4.

10. A lithium ion battery, characterized in that: The positive electrode sheet according to claim 9 is used as the positive electrode.

Citation Information

Cited By

  • Ternary co-doped nickel-manganese-based precursor, positive electrode material, preparation thereof and battery

    CN120681805A

  • Positive electrode material and preparation method thereof, positive electrode plate, battery and electric device

    CN120824356A

  • Cathode material, preparation method thereof, cathode sheet, battery and electric device

    CN120824356B

  • Spinel lithium manganate positive electrode material and preparation method thereof

    CN122291500A

  • Spinel lithium manganate cathode material and preparation method thereof

    CN122291500B